The Impact of Climate Change on Tourism Demand in China - Jong, Meng Chang; Puah, Chin Hong; Mohammad Affendy, Arip (International Journal of Energy Economics and Policy (IJEEP), 2024)
This paper aims to examine the climatic impact on the demand of international tourism industry in China. Due to rising awareness and urgency to combat climate change, there is a growing need to better grasp the possible implications and the risk of climate change to the tourism industry. The tourists’ travel decision can be influenced by both climatic and non-climatic factors, and thus this study has integrated both factors into the models. The climatic variables are represented by Tourism Climate Index (TCI) and Holiday Climate Index (HCI) while the selected non-climatic determinants are tourists’ income, tourism price, exchange rate and transportation cost. The empirical findings showed that climate conditions significantly and adversely affect China’s tourism demand. Tourists’ income level, as expected, positively affects their decision to travel to China. Meanwhile, the tourism price, exchange rate, and transportation cost negatively impact China’s tourism industry. Although some valuable results have been found, more works are required to understand its long-haul significance to the tourism industry, especially during extreme events such as extreme weathers, pandemics, financial crises and etc.